(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article is devoted to the study of the theoretical and practical foundations of improving communicative strategies as a management tool in the military education system. It analyzes the transformation of the management paradigm in modern military educational institutions, the systemic characteristics of communicative processes, and the mechanisms of interaction at the strategic and operational levels. The communicative competence of a military leader, the harmony of vertical and horizontal communications, and the effectiveness of feedback mechanisms are substantiated in terms of their impact on the quality of education and disciplinary stability.